“Not just students in need”: Findings from a nominal group technique study of what parents want in an Australian school-provided meal system - Alexandra C. Manson; Rebecca K. Golley; Dimity C. Dutch; Brittany J. Johnson (Australian and New Zealand Journal of Public Health)
Objective: Interest in national adoption of school-provided meals is growing across Australia; however, parent perspectives are not well understood. This study aimed to understand the most important features of a potential school-provided meal system to parents of primary school children in Australia. Methods: Virtual Nominal Group Technique workshops with Australian caregivers of primary school-aged children were held to identify, discuss and prioritise features. Discussions were noted and collated collaboratively with participants, with quotes collected. Top voted features were scored using relative importance. Results: Five workshops with 25 total participants identified 28 diverse features, with interest in a comprehensive, well-designed system. Priority features were nutrition (importance score 0.46), cost (0.42), stigma considerations (0.32), catering to dietary requirements (0.29) and sustainability and waste (0.25). Conclusions: Findings demonstrated the diverse considerations for a parent-accepted school-provided meal. Prioritised features align with initiatives internationally and locally, indicating feasible strategies to inform an acceptable Australian school food transformation. Implications for public health: Provision of universally available, accessible and nutritious meals aligns with parent values and creates opportunity for public health impact. Findings can be used to inform the design of school food programs, supported by implementation strategies used internationally and locally, conducive to optimum child and parent health outcomes.